(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
A mobile ad hoc network (MANET) consists of wireless mobile nodes without having a fixed infrastructure. The communication between these mobile nodes is carried out without any centralized control. The communication among the nodes within the infrastructure less networks is done through some routing protocol. But whenever any mobile node want to communicate a node in a network that is outside the ad hoc network such as internet, there should be an appropriate mechanism for establishing this connection. Gateway discovery is a fundamental process in connecting MANET with the internet. A mobile node can connect to the internet by discovery of some specialized nodes called as gateway nodes These Gateway nodes act as a bridge between the mobile ad hoc networks and the internet. The basic aim of the gateway discovery approach is to modify the route discovery process so that it is not only used for discovery of destination mobile nodes but also the gateways. In this paper we are going to present a review of various gateway discovery approaches which are used for establishing the interconnection of mobile ad hoc networks and internet.